2001
DOI: 10.1177/147323000102900611
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Roxithromycin in the Lesions of Acne Vulgaris

Abstract: Roxithromycin, a macrolide antibiotic, is used in the treatment of acne vulgaris, although there have been no reports on its concentration in lesions when administered orally. We investigated the concentration of roxithromycin in acne vulgaris lesions in five patients who received 150 mg roxithromycin orally twice daily for 2 weeks. The mean concentration of roxithromycin in the lesions was 0.54 microgram/ml. These results suggest that roxithromycin accumulates at therapeutic levels in the pilosebaceous system. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Other antimicrobials were essentially ineffective or weakly effective in inhibiting these cytokine productions, while at the highest drug concentration, GM-CSF and IL-6 production was inhibited by both roxithromycin and erythromycin, and by roxithromycin and clindamycin, respectively. tions of other antimicrobials used in the present study were reported previously [25,26].…”
Section: Ndfx Inhibits the Proinflammatory Cytokine Production By Kermentioning
confidence: 85%
“…Other antimicrobials were essentially ineffective or weakly effective in inhibiting these cytokine productions, while at the highest drug concentration, GM-CSF and IL-6 production was inhibited by both roxithromycin and erythromycin, and by roxithromycin and clindamycin, respectively. tions of other antimicrobials used in the present study were reported previously [25,26].…”
Section: Ndfx Inhibits the Proinflammatory Cytokine Production By Kermentioning
confidence: 85%
“…It accumulates at therapeutic levels in the pilosebaceous system [90]and exhibits an interesting spectrum of effects, namely direct anti-inflammatory and anti-androgenic activities. It significantly inhibits the production of lipase and neutrophil chemotactic factor by P. acnes as well as of P. acnes -induced NF-kB activation at concentrations much lower than the MIC at which the growth curve of P. acnes is not affected [34, 91].…”
Section: New Developments and Future Trendsmentioning
confidence: 99%